Development of a LIDAR array to study and classify wakes at the U.S. Department of Energy (DOE)/Sandia National Laboratories Scaled Wind Farm Technology (SWiFT) facility. Issue 1 (February 2019) - Pereira, Tassia Penha; Pol, Suhas; Ruiz-Columbie, Arquimedes; Westergaard, Carsten
Wind turbine wake has the wind speed deficit and the increased turbulent flow to the downstream turbines as signatures. Various experiments and simulations have been performed over the years to investigate the wake parameters; however, a statistical characterization of wake states is still to be uncovered. An innovative wake measurement approach that uses five ground-based Spidar Light Detection and Ranging (LIDAR) has been developed in partnership with Texas Tech University (TTU), Sandia National Laboratories, and Pentalum Technologies to develop, test, and validate a system and methodology that enables the capture of statistically significant wake dynamics in real atmospheric conditions. This article will discuss the potential of this new direct detection remote sensing equipment for studying the wake states as well as report the validation process of the LIDAR and the feasibility of continuing to pursue the primary purpose of the initiative.